Computer-generated artificial life model: algorithm for hunters hunting preys - Haque, Md. Mahbub-Ul; Sur, Surid Imam Khan; Shahriar, Rehnuma Binta; Saha, Supti Rani (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.